Stunting Prevention Based on Collaborative Governance in Sumedang Regency, Province West Java - Risa Mayangsari; Petrus Polyando; Imelda Hutosoit (Jurnal Scientia, 2024)
Stunting is a national issue that is of public concern, not only the Government but all elements, both the private sector and society. Stunting is one of the most crucial health problems that occurs even in various countries in the world, this is also the case with Sumedang Regency as one of 100 regencies/cities with stunting intervention which has reached 27.6% in 2022. The aim of this research is to find out collaborative governance-based stunting prevention process in Sumedang Regency. This research uses primary data from interviews and secondary data from documents and reports as well as regulations related to stunting prevention. This study used descriptive qualitative method. In collecting data, researchers carried out observations, interviews and collected documents regarding stunting prevention that has been carried out by Sumedang Regency. The research results show that collaborative governance in accelerating stunting prevention in Sumedang Regency has been running well and effectively. This is based on analysis of indicators of a collaborative governance approach, namely initial conditions, institutional design, facilitative leadership and collaboration processes. Where the interim results obtained were a decrease in the stunting prevalence rate in the simultaneous weighing results in February 2024, namely 8.21%.